Comprehensive phenotyping of human peripheral blood B lymphocytes in healthy conditions. Issue 2 (18th October 2021) - Carsetti, Rita; Terreri, Sara; Conti, Maria Giulia; Fernandez Salinas, Ane; Corrente, Francesco; Capponi, Claudia; Albano, Christian; Piano Mortari, Eva
Abstract: The B cell compartment provides innate and adaptive immune defenses against pathogens. Different B cell subsets, reflecting the maturation stages of B cells, have noninterchangeable functions and roles in innate and adaptive immune responses. In this review, we provide an overview of the B cell subsets present in peripheral blood of healthy individuals. A specific gating strategy is also described to clearly and univocally identify B cell subsets based on the their phenotypic traits by flow cytometric analysis.